The practical astronomer explore the wonders of the night sky - Gater, Will ca. 20./21. Jahrhundert (DorlingKindersley, 2020)
Discover the wonders of the Universe with this complete introduction to observing and understanding the night sky
Includes index
Keywords: Astronomische Beobachtung; Astronomy / Observers' manuals; Astronomy; SCIENCE / Astronomy; Astronomy / Handbooks, manuals, etc; Handbooks and manuals